Biological invasions economic and environmental costs of alien plant, animal, and microbe species - Pimentel, David, 1925- (Boca Raton, Fla. : CRC Press, 2011)
"A revised, expanded, and updated second version to the successful Biological Invasions: Economic and Environmental Costs of Alien Plant, Animal, and Microbe Species, this reference discusses how non-native species invade new ecosystems and the subsequent economic and environmental effects of these species. With nine new chapters, this text provides detailed information on the major components of the invasive-species problem from six continents, including impacts on human health and livestock. The book examines ways in which non-native species destroy vital crops and forests; damage ecosystem dynamics, which leads to plant and animal biodiversity losses; and cause soil erosion and water loss"--
"Some 10 million species of plants, animals, and microbes are thought to inhabit the earth, but so far only about 1.5 million of these have been identified. A mere 15 of the approximately 250,000 known plant species provide the world's human population with about 90 percent of its food.1 These crops are wheat, rice, corn, rye, barley, soybeans, and common millet. Although these crops are now grown in nearly every nation, only one or two of these crop species originated in any specific country. Among animals, eight species currently provide the bulk of the meat, milk, and eggs consumed by humans. These leading livestock species are cattle, buffalo, sheep, goats, horses, camels, chickens, and ducks. Farms in the United States feed approximately 100 million cattle, 7 million sheep, and 9 billion chickens each year"--
section 1. Australia -- section 2. Brazil -- section 3. British Isles -- section 4. Europe -- section 5. India -- section 6. New Zealand -- section 7. South Africa -- section 8. United States.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Biological invasions -- Economic aspects; Biological invasions -- Environmental aspects; Electronic books